INDONESIAN TAX REFORMS POLICY ALTERNATIVES FOR HANDLING SHADOW ECONOMY - Al-Firdaus, Farid (Polytechnic of State Finance STAN, 2023)
Indonesian Directorate General of Taxes (DGT) has been running the tax reform covering human resource development, Information and Technology (IT), process business renewal, and policy reforms since 2016 to solve tax avoidance as a shadow economy activity. To make the process efficient, DGT needs to do prioritizing. The author analyzed the best tax reforms policy by assessing the symptoms covering the system burden from 2002 to 2017, including 15x taxpayers, 2x employees, and 3.5x offices. Then, the author argued to frame the DGT’s case as mainly about government failures related to representative government and bureaucratic supply, also determining the goals, including improving taxpayers’ trust and compliance, tax administration, and tax officers’ integrity. There are criteria for assessing the achievement of the plans: service, easiness, modernness, and professionality. The policy alternatives are mutually exclusive, covering tax officers’ training, tax-administration IT system updates, Standard Operating Procedures (SOP) improvement, and regulations creation. The author found that the tax-administration IT system updates got the most significant points through a multi-goal analysis framework. However, the author suggests considering another policy, SOP improvement, which can be an alternative for solving the limited resources but not removing the better quality of taxpayers’ services.